Pengaruh Pemahaman Literasi Ekonomi Terhadap Tingkat Perilaku Konsumtif Mahasiswa Pendidikan Ekonomi UNPAS : Survei pada mahasiswa Pendidikan Ekonomi Angkatan 2020 dan 2021 FKIP UNPAS - S. Marten Yogaswara; Aini Kusniawati; Yudho Ramafrizal (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
The title of this study is the effect of understanding economic literacy on the level of consumptive behavior of Unpas economics students. This study aims to determine the effect of economic literacy on the level of consumptive behavior of Pasundan University economic education students. The research method used is a quantitative method with a survey approach to Pasundan University economics education students batch 2020 and 2021. Based on the results of the research it shows that economic literacy has a significant impact on student buying behavior. Based on the results of hypothesis testing, there is an effect of economic literacy on consumptive behavior in 48.7% of cases, while the remaining 51.3% is influenced by other factors not examined by researchers. Keywords : Economic literacy, student consumptive behavior